Effects of Phet Interactive Simulation Activities on Secondary School Students’ Physics Achievement - Najib, Mohd Nizar Mohd; Md-Ali, Ruzlan; Yaacob, Aizan (South Asian Journal of Social Sciences and Humanities, 2022)
PhET (Physics Education Technology) interactive simulation is a website-based simulation developed by simulation experts from the University of Colorado Boulder to help students learn physics through simulated learning. This research aims to examine students’ achievement after utilized simulated learning and teaching. A module and teaching plan have been specifically designed by researchers to be integrated with PhET simulation in the students’ teaching and learning processes. This research utilized a quasi-experimental design where pre-and post-tests are multiple choice type of test involved 30 students in the experimental group (using simulated learning) and 30 students in the control group (using conventional learning). The results showed that there were significant differences in pre-and post-tests means scores for the experimental group. On the other hand, the control group showed no significant differences. This proved that PhET simulation, with well-designed module and teaching plan can improve students’ achievement in physics.